Effect of combining eight weeks of neuromuscular training with dual cognitive tasks on landing mechanics in futsal players with knee ligament dominance defect: a randomized controlled trial - Hamoongard, M.; Hadadnezhad, M.; Abbasi, A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The performing of jump and landing in futsal simultaneous with divided attention is one of the most common mechanisms of non-contact anterior cruciate ligament (ACL) injury. Neuromuscular training has effectively reduced the risk of ACL injury, but the effect of neurocognitive training has received less attention. This study investigated the effect of combining 8 weeks of neuromuscular training with dual cognitive tasks on the landing mechanics of futsal players with knee ligament dominance defects.